Assessment of husbands’ involvement in birth preparedness and complication readiness: a hospital-based study - Srishti Singh; S. K. Jha; Anuj Jangra; Tanisha; Taniya; Shruti; Surbhi Mohan (International Journal Of Community Medicine And Public Health, 2026)
Background: The journey to parenthood starts well before conception and demands righteous involvement of both partners to achieve favourable pregnancy outcomes. BPACR may be influenced by male-partner engagement because husbands are the family’s most powerful decision-makers and their involvement may reduce maternal death by avoiding delays through a well-planned birth and complication readiness. The present study was undertaken to assess the knowledge and role of husbands in birth preparedness and the reasons for lack of participation. Methods: This hospital based cross-sectional study was conducted among 141 husbands (aged >21 years) of recently delivered postpartum women who were admitted and delivered in the hospital in 2023. A semi-structured interview schedule was used for data collection. Results: It was found that around half of participants had knowledge of danger signs while 85.1% and 87.2% identified skilled SBA and transportation for delivery respectively. 70.2% wives were satisfied with their husband’s support. Knowledge of danger signs, insisting ANC, arranging food/clothes, allowing wife to rest and providing emotional support had significant association with wives’ satisfaction. The commonest reasons for lack of participation were that men were not allowed to enter labour room (31.9%) and busy arranging food and money (25.5%). Conclusions: It was found that husbands showed high readiness in logistics and emotional support and active participation in chores. Majority of wives were satisfied with their husband’s support which emphasizes that male involvement is not just a clinical necessity but a psychological one. Hospital and labour room policies to be more inclusive of male partners.